2015
DOI: 10.1080/17470919.2015.1006374
|View full text |Cite
|
Sign up to set email alerts
|

Doing good or bad: How interactions between action and emotion expectations shape the sense of agency

Abstract: The emotional consequences of our own and others' actions can influence our agentive self-awareness in social contexts. Positive outcomes are usually linked to the self and used for self-enhancement, whereas negative outcomes are more often attributed to others. In most situations, these causal attribution tendencies seem to be immediately present instead of involving reflective interpretations of the action experience. To address the question at which level of the cognitive hierarchy emotions and action perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 63 publications
2
29
0
Order By: Relevance
“…Our current dataset highlights an effect of emotional valence on this interoceptive learning process. Results hereby approximate findings in the exteroceptive domain (Batty and Taylor, 2003; Ishai et al , 2006) as well as studies reporting a modulating impact of valence on other internal, pre-reflective forms of bodily self-awareness such as agency (Gentsch et al , 2015; Yoshie and Haggard, 2017). …”
Section: Discussionsupporting
confidence: 87%
“…Our current dataset highlights an effect of emotional valence on this interoceptive learning process. Results hereby approximate findings in the exteroceptive domain (Batty and Taylor, 2003; Ishai et al , 2006) as well as studies reporting a modulating impact of valence on other internal, pre-reflective forms of bodily self-awareness such as agency (Gentsch et al , 2015; Yoshie and Haggard, 2017). …”
Section: Discussionsupporting
confidence: 87%
“…Our result extends previous work in two important ways. First, our effect was found for action binding , while previous studies found valence effects primarily for outcome binding (Gentsch et al 2015 ; Takahata et al 2012 ; Yoshie and Haggard 2013 , 2017 ). Action binding is potentially a more informative measure of action-outcome association than outcome binding: it is independent of the physical characteristics of the outcome event, while outcome binding is not (Wolpe and Rowe 2014 ).…”
Section: Discussionmentioning
confidence: 46%
“…In principle, scientific data on both the objective controllability of action under emotion and the subjective experience of agency should be highly relevant to this question, but, in practice, current law has not been informed by the evidence base of cognitive or brain sciences. Previous studies reported reduced sense of agency over actions that produced negative, compared to either positive or neutral, outcomes (Barlas et al 2018 ; Christensen et al 2016 ; Gentsch et al 2015 ; Yoshie and Haggard 2017 ). One might suggest, therefore, that negative emotions might cause a reduction in the sense of control over one’s own actions and their external outcomes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Using a p < .01 threshold, we found that area-specific representational precision was associated with lower scores on the Behavioral Inhibition Scale, r(28) = 0.482, p = 0.007 (cf. Gentsch et al, 2015). However this result did not survive Bonferroni or FDR correction, and is therefore not discussed further.…”
Section: Experimental Paradigm and Designmentioning
confidence: 92%